Conflict avoidance in old age: the role of anticipated loneliness - Oberhauser, Lia; Neubauer, Andreas B.; Kessler, Eva-Marie (GeroPsych, 2017)
Conflict avoidance increases across the adult lifespan. This cross-sectional study looks at conflict avoidance as part of a mechanism to regulate belongingness needs (Sheldon, 2011). We assumed that older adults perceive more threats to their belongingness when they contemplate their future, and that they preventively react with avoidance coping. We set up a model predicting conflict avoidance that included perceptions of future nonbelonging, termed anticipated loneliness, and other predictors including sociodemographics, indicators of subjective well-being and perceived social support (N = 331, aged 40-87). Anticipated loneliness predicted conflict avoidance above all other predictors and partially mediated the age-association of conflict avoidance. Results suggest that belongingness regulation accounts may deepen our understanding of conflict avoidance in the second half of life.
Gesehen am 05.04.2018